INTERFAITH MARRIAGES: IN THE LIGHT OF ISLAMIC AND SOCIOLOGICAL PERSPECTIVES - Ayesha Farooq; Muhammad Sultan Shah (Al-Qanṭara, 2023)
The present study intends to investigate the various aspects associated with interfaith marriages practiced among the Muslim communities. There are concomitant factors that need some understanding where two partners belong to different faith. Islamic teachings also differ for both men and women who wish to marry outside their belief system. In Islam, men are allowed to marry women of the book (ahl e kitab); these females belong to either Islam, Christianity or Judaism. However, Muslim women can only marry Muslim men. Various issues arise in result of such marriages, these include conversion of the spouse, socialization of the children, identity of the parents and children etc. Social and cultural elements also intersect with the lives of such couples and families. Future of the children is likely to get affected by the religious ideology they intend to follow. Forced conversions are discouraged in the Islamic ideology, however some individuals change their faith just to marry the person of their choice. Mutual understanding can make things work in married life though they face various challenges due to social and religious bindings. Regardless of the religious ideology, political and legal frameworks also have implications for the mixed marriages. Keywords: Interfaith marriage, Islamic ideology, People of book, Conversion, Social Identity, Child socialization.